Integration of palliative care in pediatric neuro-oncology: Integration of palliative care in pediatric neuro-oncology (Paliativní medicína, 2025)
Central nervous system tumors are the most common solid tumors in childhood and are associated with the highest morbidity, lethality, and symptom burden in pediatric oncology. Early integration of pediatric palliative care into oncological treatment is therefore crucial for improving the quality of life for both patients and their families. This article presents a systematic model for integrating pediatric palliative care in pediatric neuro-oncology, inspired by the framework used at St. Jude Children's Research Hospital. The model defines key milestones in the patient's disease trajectory where it is appropriate to incorporate elements of primary palliative care provided by the primary oncology team, and when to utilize specialized palliative care delivered by the Pediatric Supportive Care Team. Implementation of this model enables effective symptom management, optimization of communication, and ensures continuity of care, including family support during bereavement. The article highlights the benefits of early palliative care integration in pediatric oncology and presents a proposal for its implementation in clinical practice.
Keywords: pediatric palliative care; neuro-oncology; pediatric oncology; integration; methodology